SISTEM INFORMASI INVENTARIS BARANG BERBASIS WEB PADA SMP NEGERI 1 BUER - Novi Oktaviani; I Made Widiarta; Nurlaily (Jurnal Informatika Teknologi dan Sains, 2019)
This study aims to design and build an Information System Web-based Inventory of Goods at Buer 1 Junior High School in order to help part of the inventory of goods in borrowing goods, information on the condition of the goods, numbering of goods and data collection of transactions from the purchase of goods. The research method used is a qualitative descriptive method and data collection methods used in this study, namely the method of observation and interviews and using the Waterfall method as a method of software development. Information Based Inventory Information System Web at 1 Buer Public Middle School was built using Sublime Text language PHP programming and MySql database. Inventory Information System Web Based At SMP Negeri 1 Buer makes it easy for Inventory Admin in item numbering, data collection, information on the condition of the goods, the process of borrowing and returning goods and data collection of goods from the purchase transaction